Integration of simulation and fuzzy multi-attribute decision making for modelling and assessment of fuzzy parameters. (17th October 2010) - Azadeh, Ali; Seifoory, Maryam; Abbasi, Morteza
This article introduces a methodology to integrate fuzzy multi-attribute decision making (FMADM) and fuzzy simulation. According to this method, a fuzzy simulation method is applied to study the effect of different alternative on system's performance and decision criteria taking into account fuzzy inputs. Using a fuzzy analytical hierarchy process (FAHP) and the results of fuzzy simulation, a FMADM is conducted to select the best alternative. This article introduces how to incorporate fuzzy set theory with discrete-event simulation in order to model uncertain activity duration in simulating a real-world system, especially when insufficient or no sample data are available. A case study is developed to apply this method to select a scenario to implement preventive maintenance program in a constant work in process (CONWIP) system.